Fulfillment of The Living Rights of Children the Victims of Divorce in the Muslim Community of Lombok, Indonesia - Abdullah, Abdullah; Syahri, Akhmad; Hamamah, Fatin; Gafur, Abd.; Sholeh, Ahmad (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research examines the effectiveness of fulfilling the livelihood rights of children, the victims of divorce, the inhibiting factors, and how alternative solutions solve the problem of providing for children in Lombok Island, West Nusa Tenggara, Indonesia. This research is field research. The research data includes primary data and secondary data. The primary data is data obtained from respondents, informants, and resource persons. Data collection techniques in this research used interview techniques, observation, and documentation. The data that had been collected was inventoried and classified and then analyzed using the deductive method to draw conclusions. The results of this study indicate that fulfilling the livelihood rights of children of divorce victims in Lombok, West Nusa Tenggara, Indonesia is not very effective. Research data shows that 45% of children who are the victims of divorce are not given a living right at all, and the remaining 55% are given a living but not by the nominal needs of the children, 24% of children are given a living of 100,000-300,000 thousand per month and 31% of children who are the victims of divorce are given a living of 350,000 -500,000 thousand rupiahs. Factors inhibiting the fulfillment of children's livelihood and education rights are 42% due to negligence, 26% due to marriage, 21% family conflict, and 11% due to economic factors. An alternative solution to overcoming the problem of fulfilling children's livelihood rights is socialization law, tabayyun and deliberation, religious approach, and legal approach.